HUBUNGAN TIPE KEPRIBADIAN DENGAN KINERJA GURU PAUD SE-KECAMATAN TEMPULING KABUPATEN INDRAGIRI HILIR - Dessy Aspira; Devi Risma; Zulkifli N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This Study aims to determine the correlation between types of personality with the performance of PAUD teachers in Tempuling Subs-district Indragiri Hilir Regency. As for the population of this study was of PAUD teachers in Tempuling Sub-district which numbered 72 people. For the experimental study sample was 52. The method used in this study was quantitative correlation to see the correlation between the independent variables with the dependent variables. The data collection technique used was a questionnaire by likert scale. Data analysis techniques use a scale trial and statistical method analysis with the IBM SPSS program for windows ver. 22. The result of hypothesis showed that there was a significant positive correlation between types of personality with performance of PAUD teachers in Tempuling Sub-district Indragiri Hilir Regency. It can be know from the value of determinat coefficient produced was KD=r2x100= 0,5382x100=28,94%. The result showed that types of personality had correlation of 28,94% with teachers performance futhemore, the dominant correlation between types of personality with teacher performance was agreeableness depend on the stong category with the value of determinant coefficient produced was KD=r2x100= 0,7562x100=57,15%. It showed that agreebleness related to 57,15% of teachers performance.Key Words: Types of Personality, Teacher Performance